Meta-structure and alternative structural implementations for NVH improvements in an electromechanical system - Ozturk, Engin; Demir, Cihan (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2025)
Advancements in computer and processor technologies have enabled engineers to design complex geometrical structures using computer-aided design (CAD) software. Finite element analysis (FEA) allows for detailed investigations of complex structures in fluid mechanics, structural strength, and dynamic systems. In this study, the vibration, stiffness, and noise performance of a multi-component electromechanical product with different material properties were examined. Sources of vibration and noise under operating conditions were identified through numerical analyses and experimental measurements, allowing for their mitigation at their origin. A compact geared motor capable of generating high torque produces undesirable vibration and noise due to gear contact at low speed and high torque, thereby necessitating additional engineering measures. In this study, a free vibration analysis of the three-dimensional model, including material properties and assembly conditions, was performed. Vibration modes and natural frequencies were identified, and the FEA results were validated using experimental methods. Two approaches were implemented to reduce vibration and noise: (i) the incorporation of stiffeners and metastructures into the electronic housing to enhance surface damping, and (ii) the reinforcement of components with low rigidity. Measurements indicated that surface area modifications effectively reduced noise levels, while stiffness reinforcement resulted in only limited noise reduction. Furthermore, it was confirmed that the backlash between gears plays a critical role in vibration and noise behavior.
Keywords: Modal analysis; modal test; sound intensity; design improvement; meta-structure; Engineering